COVID-19 and Combined Diabetic Ketoacidosis and Hyperglycemic Hyperosmolar Nonketotic Coma: Report of 11 Cases - Balraj Singh MD; Parminder Kaur MD; Nicole Majachani MD; Prem Patel MD; Ro-Jay Romor Reid MD; Michael Maroules MD (SAGE Publishing, 2021)
We report 11 cases of combined diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar nonketotic coma (HHNK) in coronavirus 2019 patients who presented to our institution in New Jersey, USA. The median age was 47 years (range 12-88 years). Out of the 11 patients, 7 were male and 4 were female. Out of 11 patients, 8 had type 2 diabetes mellitus (DM), 2 had undiagnosed DM, and 1 had type 1 DM. Presenting complaints included altered mental status, weakness, shortness of breath, cough, fever, vomiting, abdominal pain, chest pain, and foot pain. Out of 11 patients, pneumonia was diagnosed at presentation in 8 patients, while in 3 patients, chest X-ray was clear. Median value of initial glucose on presentation was 974 mg/dL (range 549-1556 mg/dL), and hemoglobin A1c on presentation was 13.8%. The median value of anion gap was 34 mEq/L. Out of the 11 patients, ketonemia was moderate in 6 patients, large in 3, and small in 2 patients. Acute kidney injury (AKI) occurred in 9 patients and 2 patients required renal replacement therapy. Out of the 11 patients, 6 required mechanical ventilation and 7 patients died. All the 6 patients requiring mechanical ventilation died. Our case series shows COVID-19 infection can precipitate acute metabolic complications in known DM patients or as first manifestation in undiagnosed DM patients. Patients can present with DKA/HHNK symptoms and/or respiratory symptoms. Mechanical ventilation is a poor prognostic factor. Further studies are needed to characterize prognostic factors associated with mortality in this vulnerable patient population.